Pendidikan Karakter Anak Usia Dini sebagai Upaya Peningkatan Karakter Bangsa : Literature Review - Nurman Hidaya; Yasipin Aisna (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2020)
ABSTRACTThe decline in the quality of the nation's character is characterized by the number of cases popping up that are not in accordance with norm values such as; rampant corruption, theft, murder, rape and juvenile delinquency cases such as brawls, free sex and drug abuse, to overcome this it is necessary to character education for children from an early age. The purpose of writing to find out how to improve the character of the nation based on Evidence Based. In the process of searching literature, several databases are used such as Pubmed, NCBI, goole shoolar and sciencedirect. It is expected that parents will set an example and instill good character in children and play a useful role playing game and prevent children from seeing unfavorable characters in the environment. With character education will develop the basic potential to be kind, think well, and behave well. Strengthening and building multicultural children's behavior, enhancing the competitive civilization of students in society. Keywork: Parenting, Game Types and Character Building